2024
DOI: 10.7150/ijbs.90982
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Targeting NF-κB Pathway in Neurological Disorders: What We Know So Far?

Abdullah Al Mamun,
Chuxiao Shao,
Peiwu Geng
et al.

Abstract: Polyphenolic compounds have shown promising neuroprotective properties, making them a valuable resource for identifying prospective drug candidates to treat several neurological disorders (NDs). Numerous studies have reported that polyphenols can disrupt the nuclear factor kappa B(NF-κB) pathway by inhibiting the phosphorylation or ubiquitination of signaling molecules, which further prevents the degradation of IκB. Additionally, they prevent NF-κB translocation to the nucleus and pro-inflammatory cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 169 publications
(196 reference statements)
0
2
0
Order By: Relevance
“…They can neutralize free radicals and ROS, reducing oxidative stress, which is a significant contributor to neuronal damage in AD [ 153 ]. In vitro studies have shown that polyphenols can also modulate signaling pathways involved in cell survival and apoptosis, further contributing to their neuroprotective potential [ 154 ].…”
Section: Polyphenols and Their In Vitro Impact On Ad Treatmentmentioning
confidence: 99%
“…They can neutralize free radicals and ROS, reducing oxidative stress, which is a significant contributor to neuronal damage in AD [ 153 ]. In vitro studies have shown that polyphenols can also modulate signaling pathways involved in cell survival and apoptosis, further contributing to their neuroprotective potential [ 154 ].…”
Section: Polyphenols and Their In Vitro Impact On Ad Treatmentmentioning
confidence: 99%
“…Diet has proved to exert immunomodulatory and neuroprotective effects and limit the inflammation induced by glial cells, thus improving neurological clinical status [18]. Various studies have explored the neuroprotective role of polyphenolic compounds (e.g., resveratrol, curcumin, and pterostilbene) that can inhibit the NF-kB pathway, as well as prevent the NF-kB nuclear translocation and inflammatory cytokine production [186].…”
Section: Future Perspectivesmentioning
confidence: 99%